Morphology and Ultrastructure of Antennal Sensilla in Male and Female Agrilus mali (Coleoptera: Buprestidae). Issue 1 (22nd August 2016) - Yi, Zhihao; Liu, Deguang; Cui, Xiaoning; Shang, Zheming
Abstract: The apple buprestid beetle, Agrilus mali Matsumura, is an invasive pest causing significant damages to rare wild apple forests of Xinjiang. The morphology, abundance and distribution of antennal sensilla in both sexes of this pest were examined. We found that the antennae of A. mali females were longer than those of males. Five types of antennal sensilla were characterized, including trichodea (subtypes Tr.1, Tr.2, and Tr.3), chaetica (subtypes Sc.1, Sc.2, Sc.3, and Sc.4), basiconica (subtypes Ba. 1, Ba. 2, Ba. 3 and Ba.4), Böhm bristles (subtypes BB. 1, and BB. 2), and multiporous grooved sensilla. The most abundant sensilla of Ba.2 tended to occur mainly on flagellomeres 5–8 in both sexes. The last three flagellomeres tended to have the most abundant Tr.1 in both sexes. Overall, the abundance and distribution of these sensilla appeared to be highly conserved in both sexes, and their olfactory organs seemed to cluster on flagellomeres 6–8. However, some sex dimorphisms were also observed. Tr.3 and BB.2 were found only in females. Sensilla of Sc.2 were found on the pedicel and first two flagellomeres only in males. When compared with males, females showed a higher number of Sc.3, but a lower number of Sc.4 on the pedicel. These results indicate that contact cues could be important in intersexual communication in A. mali. The functional roles of these sensilla and their implications in A. mali behaviors are discussed, and further studies of identified chemosensitive sensilla can provide a foundation for developing semiochemical-based management strategies.